2021
DOI: 10.1037/sgd0000446
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic, authoritarianism, and rejection of sexual dissenters in Poland.

Abstract: In Poland, gender hierarchy restricting women's sexuality and hetero-normativity are rooted in traditional 'family values' supported by the teachings of the Polish Catholic Church and attached to Polish national identity. Dissenters to traditional norms regulating gender and sexual relations are rejected as threat to social order and national unity. Latent growth curve modeling performed on data from a three-wave longitudinal study indicated linear, interrelated increases in authoritarianism, a desire for nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 61 publications
4
36
1
Order By: Relevance
“…Three studies used a longitudinal design with pre- and post-pandemic measures, similar to ours. A study in Poland ( Golec de Zavala et al, 2020 ) found small increases ( d av around 0.15) in right-wing authoritarianism (conformity) and sexual prejudice (conformity), and no changes in social-dominance orientation (cooperation) or political conservatism (ambiguous). A study in the United Kingdom ( Fischer et al, 2020 ) found a very small increase ( d av around 0.05) in right-wing authoritarianism (conformity) and no change in social-dominance orientation (cooperation).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three studies used a longitudinal design with pre- and post-pandemic measures, similar to ours. A study in Poland ( Golec de Zavala et al, 2020 ) found small increases ( d av around 0.15) in right-wing authoritarianism (conformity) and sexual prejudice (conformity), and no changes in social-dominance orientation (cooperation) or political conservatism (ambiguous). A study in the United Kingdom ( Fischer et al, 2020 ) found a very small increase ( d av around 0.05) in right-wing authoritarianism (conformity) and no change in social-dominance orientation (cooperation).…”
Section: Discussionmentioning
confidence: 98%
“…Note that although no prior experimental or longitudinal work has examined the effect of disease threat on moral foundations, there are several such studies of how various related constructs (e.g., social conservatism, political conservatism, right-wing authoritarianism, social-dominance orientation, gender stereotypes, and sexual prejudice) were affected by the COVID-19 pandemic ( Fischer et al, 2020 ; Golec de Zavala et al, 2020 ; Karwowski et al, 2020 ; Rosenfeld and Tomiyama, 2021 ) and the 2014 Ebola outbreak in the United States ( Beall et al, 2016 ; Inbar et al, 2016 ; Schaller et al, 2017 ; Tiokhin and Hruschka, 2017 ). These studies have yielded a mix of small effects and null effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TMT provides a solid theoretical lens through which to better understand the impact of the pandemic on what used to be understood about life, and the ever‐changing landscape as a result of a pervasive existential threat. Researchers have examined effects on the workforce (and existential repercussions of job loss, e.g., Blustein & Guarino, 2020 ), increases in rejection of dissimilar others (Golec de Zavala, Bierwiaczonek, Baran, Keenan, & Hase, 2020 ), heightened ideological defensiveness (Su & Shen, 2020 ), the adoption of pandemic‐related health behaviours as a newly engrained part of culture (e.g., social distancing, Fairlamb & Courtney, 2021), and long‐term implications for mental health (Saltzman, Hansel, & Bordnick, 2020 ). Generally, the TMT‐based studies conducted thus far highlight a consistent narrative: the existential threat of COVID‐19 provokes individuals to strengthen their commitment to cultural ideologies.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies used a longitudinal design with pre-and post-pandemic measures, similar to ours. A study in Poland found small increases in right-wing authoritarianism and sexual prejudice (d av around 0.15) and no changes in social-dominance orientation or political conservatism (Golec de Zavala et al, 2020). A study in the United Kingdom found a very small increase in right-wing authoritarianism (d av around 0.05) and no change in social-dominance orientation (Fischer et al, 2020).…”
Section: Comparison To Other Studies Of the Covid-19 Pandemicmentioning
confidence: 99%